The Effect of Air Transportation on Regional Economic Development: Evidence from Indonesian Regencies - A. Aunurrofik (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2018)
This study aims to examine the importance of air transportation on regional development in Indonesia as an archipelago and developing country. Using cross-section dataset in regencies level and multiple regression analysis, we found that the number of flight, air passenger, and air cargo give positive and significant impact on regional per capita income. The effect of air cargo is the strongest, which imply that airport will provide the more substantial impact on regional economic growth if the airport is intended to use for trade and business activities. The motivations of regency to have an airport are if Regency is an independent island, manufacturing industry with its high-skilled and mid-skilled workers, and tourism sector.DOI: 10.15408/sjie.v7i1.6178